The impact of water and sediment quality on the health of Oreochromis Mossambicus (Peters, 1852) and Schilbe Intermedius Ruppell, 1832 at the Phalaborwa Barrage in the Olifants River - Gohell, Ashla Fiona (University of Limpopo, 2014)
The Olifants River is presently one of the most threatened river systems in South Africa. The Upper and Middle catchments are heavily impacted by anthropogenic activities, however little is known of the status of the river in the Lower catchment in the Limpopo Province. Thus the aim of this study was to evaluate the impact of water quality on the health of Oreochromis mossambicus and Schilbe intermedius at the Phalaborwa Barrage. This was achieved through assessing the water (seasonally) and sediment quality (bi-annually) at three sites in the Phalaborwa Barrage (inflow, middle and the wall). Ten specimens of each of the two selected fish species were seasonally collected using gill nets of different mesh sizes from May 2010 to January 2011. The water, sediment and the dorsal muscle tissues from both fish species were analysed for selected metals at an accredited laboratory by means of ICP-OES spectrometry and the human health risk factor upon consumption of fish contaminated with metals was assessed. Fish health was determined at the field laboratory by applying the HAI, PI and IPI. In addition, the condition factor (CF) was determined for the selected fish species during all seasons. All water constituents with the exception of turbidity during spring (wall), anions (Cl, F and SO4) and cations (Ca, K, Mg and Na) fell within the target water quality range (TWQR) for aquatic ecosystems throughout the study. Inorganic nitrogen concentrations showed eutrophic (spring) and oligotrophic conditions (autumn, winter and summer), while phosphorus indicated eutrophic (autumn, winter and spring) and hypertrophic (summer) conditions throughout the study. There was no significant difference in anions (F=0.07; df=3; p=0.97), cations (F=0.57; df=3; p=0.64) and nutrients (F=0.79; df=3; p=0.56) detected in water. The metals that were detectable in the water samples were: Al, Fe, Sn, B, Sr, Se, Ba, Mn, Sb and As, while in sediment all metals (Fe, Al, Ti, Mn, Ba, B, Zn, Ag, V, Cr, Ni, Sr, Sn, Co, Cu, Cd, Pb, As and Sb) were detected with the exception of Se. The average metal concentrations detected above the TWQR are; Al, Fe, Se, Sn, Sb and As, in the sediment only Cr and Cd were above suggested quality guidelines. There was no significant difference in metals detected in water (F=0.05; i df=3; p=0.98) and sediment (F=1.62; df=1; p=0.21). Higher HAI values were recorded for S. intermedius than O. mossambicus, indicating that O. mossambicus was in better health than S. intermedius. For S. intermedius, parasites contributed the most to the total HAI followed by abnormal liver conditions, haematocrit levels (internal variables) and abnormal gills (external variable). While for O. mossambicus, parasites, liver, haematocrit (internal variables), gills, eyes, fins and skin (external variables) contributed to the HAI values. There was no significant difference in HAI values for O. mossambicus (F=1.9; df=3; p=0.15) and S. intermedius (F=2.58; df=3; p=0.66) throughout the study. The PI and IPI for ectoparasites for both fish species, were higher than the PI for endoparasites. There was a significant difference for PI values of O. mossambicus (F=0.07; df=3; p=0.041) and S. intermedius (F=3.65; df=3; p=0.019) during the study. Oreochromis mossambicus had higher CF values than S. intermedius and both fish species had values that indicated good fish. Metals that were detectable in O. mossambicus muscle tissue included: Ba, B, Zn, Fe, Sr, Al, Mn, Cr, Ag, Pb, Ni, Cu, Se, V, Sb, Ti, Sn and Co, while for S. intermedius Ba, B, Zn, Fe, Al, Cr, Sr, Mn, Cu, As, Pb, Se, Sn, Ag, Ti, Ni, Sb and Co were recorded. There was no significant difference in bioaccumulation levels between the two fish species (F=1.412; df=3; p=0.250). The human health risk assessment indicated that fish muscle tissues are unsuitable for continuous (weekly/daily) consumption. As some carcinogenic metals i.e. Pb, Cr and Sb for O. mossambicus and Pb, As and Cr for S. intermedius were detected at HQ levels of more than 50 times the recommended value of one. In conclusion, the Phalaborwa Barrage is impacted by metals (Al, Fe, Se, Sn, Sb and As) and occasionally with nutrients. The water and sediment quality and metal bioaccumulation have confirmed the latter statement and to a lesser extent the HAI, PI and IPI. The human risk assessment done indicated that continuous consumption of fish by humans, especially O. mossambicus may have adverse effects on the health of humans.
Thesis (MSc. (Zoology)) -- University of Limpopo, 2014
Keywords: Water quality; Fish species; 553.7; Water quality -- South Africa -- Limpopo; River sediments -- Quality; Olifants River (South Africa); Phalaborwa Barrage; Mozambique Tilapia